Stress and coping in institutionalized and non-institutionalized children - Gómez Maqueo, Emilia Lucio (2016)
A study was carried out in order to know the differences in the level of stress experienced by institutionalized children, and also to know the types and coping strategies employed by them in comparison with non-institutionalized children. Also, the influence of stress in coping was analyzed by a lineal regression. Participants were 126 children (65 institutionalized and 61 non-institutionalized, age M = 10 years, age range 8 to 12 years. Children Stress Scale (EIE), Children Coping scale (EIA) and a socio-demographic profile were administered. The results showed higher levels of stress in institutionalized children compared to their non institutionalized peers (t = 3.298, P = 0.001) Statistically significant differences were obtained also in the types and the strategies that both groups employ to address their problems. The regression analysis showed that stress predicts dysfunctional and emotional coping strategies with respect to institutionalized children. These results have important implications for child socio-emotional development and hence the importance of early intervention in the population of institutionalized children is a priority.